Bacterial Luciferase Gene Cassette as a Real-time Bioreporter for Infection Model and Drug Evaluation - Wang, Xiwen; Chi, Hang; Zhou, Bo; Li, Wenliang; Li, Zhiping; Xia, Zhiping (Current Pharmaceutical Design, 2018)
The bacterial luciferase gene cassette (lux) is an ideal bioreporter for real-time monitoring of the dynamics of bacteria because it is a fully autonomous, substrate-free bioluminescent reporter system available in a prokaryotic or eukaryotic host background. The lux operon is emerging as a powerful bioreporter for the study of a wide range of biological processes such as gene function, drug discovery and development, cellular trafficking, protein-protein interactions, and especially tumorigenesis and cancer treatment. Furthermore, the use of a high signal to noise bioluminescent bioreporter is quickly replacing traditional fluorescent bioreporter because of the lack of endogenous bioluminescent reactions in living animals. This review briefly describes how the lux operon is used for bioluminescence imaging. Current advances in bioluminescence bacteria development are summarized, focusing on their construction strategy and applications in bacterial infection and antibiotic treatment. Different construction methods of lux-expressing cell lines are also discussed. Taken together, this review provides valuable guidelines toward the development of an ideal bioluminescent bacteria or cell lines to evaluate the efficacy of a drug.
Keywords: antibiotics treatment